Perencanaan Wisata One Day Trip (ODT) - Nur Fitriani; Mukti Ali; Sri Aliah Ekawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2017)
Jeneponto Regency has tourism potential that can be used as potential tourism objects, one of which is Libukang Island which is designated as a natural tourism area because it has the potential to support one day trip (ODT) tourism activities. The purpose of this study was to determine the potential and problems of one day tirp tourism, to determine the suitability and carrying capacity of tourism activities and to develop the concept of a one day trip tourism planning on Libukang Island. The analytical method used in this study is the analysis of potentials and problems that aims to find out the potential of tourism that can be developed and the problems found on Libukang Island, scoring aims to determine the suitability level of tourism to be developed, carrying capacity aims to determine the maximum number of visitors that can accommodated, spatial which aims to describe the pattern of a spatial phenomenon so that it can be well understood and zoning of the area which aims to produce a zone plan for one day trip tourism area on Libukang Island. Existing tourism object that is boating with a suitability level is very potential. Attractions that have the potential to be developed are snorkeling, swimming and beach recreation. Besides that, the tourism of the fishing village and gardening arrangement is also quite potential to be developed. The integrated one-day tourism area development plan for Libukang Island is an alternative plan for the travel route and tourism component planning.